Performance of meat purpose hybrid chicken under intensive system - Tamang, D. T.; Sharma, M. P.; Barsila, S. R. (Journal of the Institute of Agriculture and Animal Science, 2018)
A study was carried out at Livestock farm, IAAS, Chitwan, Nepal in 2011 to identify the best compatible genotypes of hybrid male parents with available breeds of female chicken for the meat production. The measureable traits were egg weight, day old chick weight, feed consumption, body weight gain, infertility, hatchability, feed conversion ratio and meat quality. Research results revealed that the Black Australorp were the best performer with respect to egg size (57.50±0.95 g.) compared with other breeds such as Sakini, New Hampshire and Lohmann Brown. The highest body weight of chicks at eight weeks age was observed in the case of F1 progenies of LIR crossed with New Hampshire (1388.33±44.57 g.). On female lines, Sakini (1211.50±48.82 g.) and Black Australorp (1404.50±48.82 g.) were found the best compatible with Cobb 500. On other hand, New Hampshire (1388.33±44.57 g.) and Lohmann Brown (1334.54±46.55 g.) were observed the best compatible with LIR while considering body weight until 8th week of age observed. The Black Australorp hen compared fairly well with comparison to other female lines in terms of growth up to eight weeks of age. Although, the F1 progenies of LIR and Cobb 500 grew faster, on the basis of FCR, the progenies of Giriraja crossed with Black Australorp (2.63) was observed good performer, which indicated that if the feed consumption could be increased, progenies of Giriraja crossed with Black Australorp will be the best compatible breeds for meat production. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, Page: 187-194